The mycotoxin beauvericin induces oocyte mitochondrial dysfunction and affects embryo development in the juvenile sheep. Issue 10 (13th August 2019) - Mastrorocco, Antonella; Martino, Nicola Antonio; Marzano, Giuseppina; Lacalandra, Giovanni Michele; Ciani, Elena; Roelen, Bernard A. J.; Dell'Aquila, Maria Elena; Minervini, Fiorenza
Abstract: Beauvericin (BEA) is a mycotoxin produced by Beauveria bassiana and Fusarium species recently reported as toxic on porcine oocyte maturation and embryo development. The aim of this study was to assess, in the juvenile sheep, whether its effects are due to alterations of oocyte and/or embryo bioenergetic/oxidative status. Cumulus‐oocyte‐complexes (COCs) were exposed to BEA during in vitro maturation (IVM), evaluated for cumulus cell (CC) apoptosis, oocyte maturation and bioenergetic/oxidative status or subjected to in vitro fertilization (IVF) and embryo culture (IVEC). Oocyte nuclear maturation and embryo development were assessed after Hoechst staining and CC apoptosis was analysed by terminal deoxynucleotidyl transferase‐mediated dUTP nick‐End labeling assay and chromatin morphology after Hoechst staining by epifluorescence microscopy. Oocyte and blastocyst bioenergetic/oxidative status were assessed by confocal microscopy after mitochondria and reactive oxygen species labelling with specific probes. BEA showed various toxic effects, that is, short‐term effects on somatic and germinal compartment of the COC (CCs and the oocyte) and long‐term carry‐over effects on developing embryos. In detail, at 5 µM, it significantly reduced oocyte maturation and immature oocytes showed increased late‐stage (Type C) CC apoptosis and DNA fragmentation while matured oocytes showed unaffected CC viability but abnormal mitochondrial distribution patterns. At lower tested concentrations (3–0.5 µM), BEA did not affect oocyte maturation, but matured oocytes showed reduced mitochondrial activity. At low concentrations, BEA impaired embryo developmental capacity and blastocyst quality after IVF and IVEC. In conclusion, in the juvenile sheep, COC exposure to BEA induces CC apoptosis and oocyte mitochondrial dysfunction with negative impact on embryo development. Abstract : Beauvericin (BEA), an emerging mycotoxin, was shown to induce various toxic effects on sheep oocytes. At 5 µM, it significantly reduced oocyte maturation, immature oocytes showed increased cumulus cell (CC) apoptosis and matured oocytes showed altered mitochondrial distribution patterns. At lower tested concentrations (3–0.5 µM), it did not affect oocyte maturation, but matured oocytes showed reduced mitochondrial activity and embryo developmental capacity and blastocyst quality after in vitro fertilization and embryo culture were impaired. In conclusion, in the juvenile sheep, cumulus‐oocyte complex exposure to BEA during in vitro maturation induced CC apoptosis and oocyte mitochondrial dysfunction thus affecting embryo development and quality.